Nutrient composition and sensory attributes of beef from grain-finished steers and heifers - Acheson, Rebecca Jean, author; Woerner, Dale R., advisor; Tatum, J. Daryl, committee member; Engle, Terry E., committee member; Belk, Keith E., committee member; Bunning, Marisa L., committee member (Colorado State University. Libraries, 2013)
Over the past decade, nutrient composition of beef became an increasingly important topic both domestically and internationally for the beef industry and its consumers. Beef is an important source of protein, monounsaturated fatty acids, conjugated linoleic acid, vitamins and minerals. Due to evolutionary changes in production practices and fabrication techniques the current nutrient data in the USDA National Nutrient Database for Standard Reference has become outdated. The objectives of these studies were to determine the nutrient composition of ten beef loin and round retail cuts to update the USDA National Nutrient Database for Standard Reference (SR). Seventy-two carcasses representing a national consist of yield grade, quality grade, and genetic type were identified from six regions across the U.S. Beef short loins, strip loins, tenderloins, inside rounds, and eye of rounds (IMPS # 173, 175, 190A, 169A, and 171C) were collected from the selected carcasses and shipped to three university meat laboratories for storage, retail fabrication, and raw/cooked analysis of nutrients. Sample homogenates from each animal were analyzed for proximate composition, as well as fatty acid, cholesterol, vitamin, and mineral content. Data from this study were intended to update SR information regarding the nutrient status of beef and to determine the influence Quality Grade, Yield Grade, and sex classification have on proximate composition. This study identified four Upper Choice, seven Low Choice, and eight Select cuts that qualify for the lean nutrient claim based on cooked separable lean values. Results from the cooked beef loin samples indicate that beef is a good source of iron, vitamin B2, and phosphorus, and an excellent source of selenium, zinc, and vitamins B3, B6, and B12. The nutrient data provided will be utilized to help update nutritional labels of beef products and to help design future dietary interventions that include beef as a protein source.
Keywords: loin; round; quality grade; maturity; nutrient; beef